Developing river tourism on the Petagas River, Sabah: Understanding community perceptions and potential level of engagement - Fiffy Hanisdah Saikim; Grace Ing Phang; Marry Tracy Pawan; Nazia Abdul Kadar; Muhammad Ali Syed Hussein; Norhuda Salleh; Nordiana Mohd. Nordin; Nor Akmar Abdul Aziz; Bruce Prideaux (Research Square, 2023)
Pollution-free rivers with protected riverbanks offer considerable scope for tourism development. In recent decades there has been increasing interest in rivers as a tourism resource. Globally, the demand for river cruising and water sports has grown rapidly as has the development of riverbanks for tourism purposes including accommodation, restaurants, and shopping. However, the role of local communities attitudes and perceptions in the development of river tourism is crucial to developing a successful tourism resource. The purpose of this study was to investigate the perceptions of local residents regarding the development of river tourism on the Petagas River, Kota Kinabalu, Sabah, Malaysia. Face-to-face semistructured interviews were undertaken with 79 residents of river communities to explore their perceptions of river tourism development on the Petagas River, assess their views on their likely participation in river tourism, and identify problems they thought might inhibit tourism development. The results show that while respondents were generally supportive of tourism development, they did recognise the need for river ecosystem restoration and the need to change many of the ways they currently use the river.